The well-preserved Late Neolithic dolmen burial of Oberbipp, Switzerland. Construction, use, and post-depositional processes. (April 2022) - Ramstein, Marianne; Steuri, Noah; Brönnimann, David; Rentzel, Philippe; Cornelissen, Marcel; Schimmelpfennig, Dirk; Anselmetti, Flavio S.; Häberle, Simone; Vandorpe, Patricia; Siebke, Inga; Furtwängler, Anja; Szidat, Sönke; et al.
Highlights: Multidisciplinary analyses link archaeology, anthropology and environmental studies. Fluvial sediments protect rare remains in Neolithic funerary monument. Megalithic construction was built in late 4th millennium BC from erratic boulders. Swiss dolmen served as collective burial place of early farming society. Palaeogenetics and bioarchaeology of 42+ individuals suggest a virilocal society. Abstract: Excavation of the Late Neolithic dolmen of Oberbipp BE, Steingasse in the Swiss Central Plateau provided a unique opportunity for a comprehensive study of the archaeological and anthropological evidence. In multidisciplinary studies, we investigated the processes at work during construction, use, and abandonment of the megalithic structure, as well as the dietary habits, subsistence strategy, and possible mobility of the Neolithic population. Archaeological methods included micromorphology, archaeobiology, typology, use-wear analysis, and geology. The anthropological investigation was complemented by an analysis of stable isotope ratios and palaeogenetics. Local topography and the cover of alluvial sediments ensured an extraordinary conservation of the monument. It allowed the preservation of the human remains of at least 42 individuals of both sexes and all ages. The observation of the sedimentary and post-depositional processes, supplemented by an extensive series of radiocarbon dates, allowed us to reconstruct the history of the dolmen in its environment and the definition of at least two deposition phases. We found genetic evidence of lactase intolerance, a local population with a mixed ancestry of early Anatolian farmers and Western hunter-gatherers, and a crop-based diet. Sparse remains of a nearby Late Neolithic settlement sustain the interpretation that this is the burial site of a local farming community. Evidence of higher mobility of females and kinship over three generations solely in the paternal line suggests a virilocal community. Bone-altering pathologies support the assumption of a caring society.